A nitrogen-containing heteroaromatic ring-containing polyamide carbon precursor-coated negative electrode material, a preparation method therefor, and applications thereof

CN123017928APending Publication Date: 2026-10-30SUZHOU NINGDIAN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611204941.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

CN114195144A公开了将三聚氰胺等含氮有机碳源与人造石墨混合后于500~1100℃煅烧制备含氮人造石墨负极材料的方法,其氮源为小分子含氮化合物或通用含氮聚合物,未涉及以主链含氮杂芳环的聚酰胺为碳前驱体的技术方案

Benefits of technology

本发明通过酰氯法、Yamazaki直接缩聚法或磷酰氯活化法制备含氮杂芳环聚酰胺前驱体,并在人造石墨表面形成氮掺杂无定形碳层。在600~700℃范围内制备的实施例中,由X射线光电子能谱N 1s分峰测得的吡啶氮占比为58%~72%。所述负极材料的0.2C可逆比容量为380~390mAh/g,同批次未包覆人造石墨为355mAh/g;5C容量相对未包覆人造石墨提高约11%~15%;0.5C下循环500圈的容量保持率为97%~98%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017928A_ABST
    Figure CN123017928A_ABST
Patent Text Reader

Abstract

The application discloses a kind of nitrogen-containing heteroaromatic ring polyamide carbon precursor coated negative electrode material and its preparation method and application, belong to lithium ion battery negative electrode material technical field.Nitrogen-containing heteroaromatic ring polyamine and aromatic polyacid or its acyl chloride are prepared into polyamide precursor by amidation polycondensation reaction, and polycondensation method includes acyl chloride method, Yamazaki direct polycondensation method and phosphorus oxychloride activation method.After polyamide precursor is coated artificial graphite particle, carbonization is carried out in inert atmosphere at 600~700 DEG C, and the negative electrode material with pyridine nitrogen doped amorphous carbon layer on surface is obtained.Pyridine nitrogen accounts for 58%~72% of total nitrogen content by X-ray photoelectron spectroscopy N 1s peak separation measurement.The capacity retention rate of the obtained material is 97%~98% at 0.5C under 500 cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery anode material technology, and in particular to a nitrogen-containing heterocyclic polyamide carbon precursor-coated anode material, its preparation method and application. Background Technology

[0002] The theoretical specific capacity of the graphite anode is 372 mAh / g. Introducing a nitrogen-doped carbon layer, especially a pyridinic-N-rich carbon layer, onto the graphite surface provides additional storage active sites for lithium ions, resulting in a reversible specific capacity higher than that of the uncoated graphite control sample. Among the three main nitrogen configurations in carbon materials, pyridinic-N, located at the edges or defect sites of graphene sheets, exhibits the strongest adsorption for Li+ and the lowest diffusion barrier, making it the most effective additional lithium storage active site.

[0003] Existing nitrogen-containing polymer carbon precursors typically form multiple nitrogen configurations simultaneously after carbonization, including pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen, making it difficult to control the proportion of pyridine nitrogen. Patent US12482831B2 (Chinese counterpart CN117756107B) discloses a method for preparing nitrogen-doped graphitized carbon materials by coating graphitized carbon with polypyrrole and annealing at high temperatures of 700–2000℃; this method is geared towards fuel cell catalyst support applications, aiming to improve the graphitization degree and stability of carbon materials, but does not address lithium-ion storage applications. CN114195144A discloses a method for preparing nitrogen-containing artificial graphite anode materials by mixing nitrogen-containing organic carbon sources such as melamine with artificial graphite and calcining at 500–1100℃; the nitrogen source is a small-molecule nitrogen-containing compound or a general nitrogen-containing polymer, but it does not involve a technical solution using polyamides with nitrogen-containing heterocyclic rings in the main chain as carbon precursors.

[0004] Pyridine-containing all-aromatic polyamides are a promising class of pyridinic-N selective carbon precursors. In the six-membered nitrogen-containing aromatic ring structure of the pyridine ring, the nitrogen in the ring is naturally in the pyridinic configuration. All-aromatic polyamides are prepared by reacting pyridine-containing aromatic diamines with aromatic diacids (or their active derivatives). The backbone of these polyamides contains a pyridine ring and an amide bond. During low-temperature carbonization at 500-700 °C, the pyridine ring nitrogen can be retained in the pyridinic-N configuration at the edge of the carbon network.

[0005] There are various methods for synthesizing all-aromatic polyamides, including: (1) acyl chloride method: the diacid is first converted into diacid chloride, and then polycondensed with diamine in a polar aprotic solvent at low temperature; (2) direct polycondensation method: the diacid and diamine are directly activated in solution using condensing agents such as triphenyl phosphite (TPP) for polycondensation (Yamazaki-Higashi method); (3) phosphoryl chloride activation method: the diacid is activated in situ with phosphorus oxychloride or diphenylphosphine chloride. These methods have been widely used in the aramid industry.

[0006] Aromatic diamines containing a pyridine ring exist in various isomers (such as 2,6-, 2,4-, 3,5-, 2,3-, 2,5-, and 3,4-diaminopyridine), and their substitution positions affect the nucleophilic activity of the amine, the polymer chain conformation, and the retention rate of pyridinic-N after carbonization. Nitrogen-containing heterocyclic diamines also include diaminopyrimidine, diaminopyrazine, triaminopyridine, and melamine, with varying nitrogen densities. Aromatic diacids containing a pyridine ring also exist in various isomers (such as pyridine-2,6-, 2,5-, and 3,5-dicarboxylic acid).

[0007] To date, there have been no reports on a technical solution that systematically utilizes various combinations of nitrogen-containing heterocyclic aromatic diamines and aromatic diacids to prepare pyridine-ring-containing fully aromatic polyamides through different amidation polycondensation methods, and then uses these polyamides to coat graphite anode particles before low-temperature carbonization to directionally construct a pyridinic-N-rich carbon layer to improve the specific capacity of graphite anodes. Summary of the Invention

[0008] This invention provides a nitrogen-containing heterocyclic polyamide carbon precursor-coated anode material, its preparation method, and its application. The precursor is prepared by amidation polycondensation reaction of nitrogen-containing aromatic polyamine monomers and aromatic polyacid monomers. The main chain contains nitrogen-containing heterocyclic aromatic rings such as pyridine rings or pyrimidine rings and amide bonds. After coating the surface of artificial graphite particles, the precursor is carbonized to form an amorphous carbon layer rich in pyridinic-N.

[0009] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a nitrogen-containing heterocyclic polyamide carbon precursor coated anode material, the anode material comprising artificial graphite matrix particles and a pyridine nitrogen-doped amorphous carbon layer coated on the surface of the artificial graphite matrix particles; The pyridine nitrogen-doped amorphous carbon layer is formed by carbonization of a polyamide precursor; The polyamide precursor is prepared by amidation polycondensation reaction of nitrogen-containing aromatic polyamine monomer and aromatic polyacid monomer, and the main chain contains amide bonds and nitrogen-containing aromatic rings. The aromatic polyacid monomers are aromatic polyacid monomers or aromatic polyacryl chloride monomers; According to the N 1s peak determination by X-ray photoelectron spectroscopy, pyridine nitrogen accounts for more than 50% of the total nitrogen content in the pyridine nitrogen-doped amorphous carbon layer.

[0010] This invention utilizes the condensation polymerization of nitrogen-containing heterocyclic aromatic polyamines and aromatic polyacid monomers to prepare a polyamide precursor, which, after carbonization, forms a nitrogen-doped amorphous carbon layer on the surface of artificial graphite. X-ray photoelectron spectroscopy results show that pyridine nitrogen accounts for more than 50% of the total nitrogen content in this carbon layer; electrochemical testing results show that the anode material has a higher reversible specific capacity, a 500-cycle capacity retention rate, and a lower interfacial impedance compared to uncoated artificial graphite.

[0011] Furthermore, the nitrogen-containing aromatic polyamine monomer includes one or more of 2,6-diaminopyridine, 3,5-diaminopyridine, 2,4,6-triaminopyridine, and 4,6-diaminopyrimidine. Examples verified the above-mentioned pyridine ring or pyrimidine ring polyamine systems; the pyridine nitrogen ratio and surface nitrogen content of the materials obtained from different monomer systems are shown in Table 1.

[0012] Furthermore, the aromatic polyacid monomer is pyridine-2,6-dicarboxylic acid.

[0013] Furthermore, the aromatic polyacrylamide monomer includes one or more of pyridine-2,6-dicarboxylic acid chloride and terephthaloyl chloride. Examples 1, 3, 4, and 7 use pyridine-2,6-dicarboxylic acid chloride, and Example 5 uses terephthaloyl chloride.

[0014] Furthermore, at least one of the nitrogen-containing aromatic polyamine monomers and aromatic polyacid monomers contains a nitrogen-containing heterocyclic ring. This limitation ensures that the polyamide precursor backbone inherently contains a nitrogen-containing heterocyclic structure, which is a fundamental prerequisite for the directional formation of a high proportion of pyridine nitrogen configuration after carbonization.

[0015] Furthermore, the D50 of the artificial graphite matrix particles is 10-20 μm; in the embodiment, artificial graphite with a D50 of 15.2 μm is used.

[0016] Furthermore, the thickness of the pyridine nitrogen-doped amorphous carbon layer is 8–20 nm. The carbon layer thickness range obtained in the examples is shown in Table 1.

[0017] Furthermore, X-ray photoelectron spectroscopy revealed that the surface nitrogen atom content of the pyridine nitrogen-doped amorphous carbon layer was 4.5–7.5 at.

[0018] Furthermore, the pyridine nitrogen in the pyridine nitrogen-doped amorphous carbon layer accounts for more than 60% of the total nitrogen content, and the surface nitrogen atom content measured by X-ray photoelectron spectroscopy is 5 to 7.5 at.

[0019] Furthermore, the nitrogen-containing aromatic polyamine monomer is 2,6-diaminopyridine and / or 4,6-diaminopyrimidine, and the aromatic polyacid monomer is pyridine-2,6-dicarboxylic acid and / or pyridine-2,6-dicarboxylic chloride. After carbonization, the pyridine nitrogen ratio and absolute pyridine nitrogen content of the above-mentioned combined system are both at a high level.

[0020] Secondly, the present invention provides a method for preparing a negative electrode material coated with a nitrogen-containing heterocyclic aromatic polyamide carbon precursor, comprising the following steps: S1. Amidation condensation reaction of nitrogen-containing aromatic polyamine monomers and aromatic polyacid monomers is carried out to prepare polyamide precursors; This step introduces a nitrogen-containing heterocyclic monomer into the main chain of the polyamide precursor. The composition of the resulting precursor was characterized by FT-IR and elemental analysis, and its number-average molecular weight and molecular weight distribution were determined by GPC.

[0021] S2. Add the polyamide precursor obtained in S1 to the solvent, add artificial graphite matrix particles, stir, and then remove the solvent or add an antisolvent to deposit the precursor to obtain pretreated artificial graphite particles. This step involves solvent dispersion and antisolvent precipitation to deposit the polyamide precursor onto the surface of artificial graphite particles; the specific coating morphology and carbon layer thickness are characterized by SEM and HR-TEM.

[0022] S3. The pretreated artificial graphite particles are calcined in an inert atmosphere to obtain a negative electrode material coated with nitrogen-containing heterocyclic polyamide carbon precursor.

[0023] This step carbonizes the polyamide precursor on the surface of artificial graphite to form a nitrogen-doped amorphous carbon layer. The pyridine nitrogen content and carbonization yield at different carbonization temperatures are shown in Table 1. Figure 7 .

[0024] Further, in step S1, the molar ratio of the nitrogen-containing aromatic polyamine monomer to the aromatic polyacid monomer is 1:(0.7-1.0). For the trifunctional polyamine system, the functional group equivalent ratio of the amino group of the nitrogen-containing aromatic polyamine monomer to the carboxyl or acyl chloride group of the aromatic polyacid monomer is 1:(0.45-1.0).

[0025] Further, in step S1, the amidation polycondensation reaction includes any one of the following: acyl chloride method, Yamazaki direct polycondensation method, and phosphoryl chloride activation method. Examples 1, 2, and 8 respectively provide the specific preparation conditions of the above three methods and the characterization results of the obtained polyamide precursors.

[0026] Further, the specific steps of the acyl chloride method are as follows: under an inert atmosphere, nitrogen-containing aromatic polyamine monomers are dissolved in a polar aprotic solvent, an inorganic salt co-solvent is added, the mixture is cooled to 0-10°C, aromatic polyacyl chloride monomers are added, the mixture is reacted at room temperature for 2-8 hours, an acid-binding agent is added, precipitation is carried out, filtration is performed, washing is performed, and drying is carried out to obtain a polyamide precursor.

[0027] Furthermore, the polar aprotic solvent is NMP; the inorganic salt co-solvent is LiCl, and its amount is 3% to 8% of the mass of NMP; the acid-binding agent is triethylamine; the aromatic polyacrylamide monomer can be prepared by reacting the corresponding aromatic polyacid with thionyl chloride, or commercially available products can be used directly.

[0028] Further, the specific steps of the Yamazaki direct polycondensation method are as follows: Aromatic polyacid monomers and nitrogen-containing aromatic polyamine monomers are added to a polar aprotic solvent, along with a condensing agent, pyridine, and an inorganic salt co-solvent. The mixture is reacted at 80–120°C for 3–8 hours, followed by precipitation, filtration, washing, and drying to obtain the polyamide precursor. This method utilizes triphenyl phosphite to activate the carboxyl groups of the aromatic polyacid in the presence of pyridine, and then condenses it with the nitrogen-containing aromatic polyamine to form the polyamide precursor.

[0029] Further, the polar aprotic solvent is NMP; the inorganic salt co-solvent is LiCl, and its amount is 3% to 8% of the mass of NMP; the condensing agent is triphenyl phosphite, and pyridine is added. Example 2 shows the FT-IR and GPC results of the precursor obtained by this method.

[0030] Further, the specific steps of the phosphoryl chloride activation method are as follows: add aromatic polyacid monomers and nitrogen-containing aromatic polyamine monomers to a polar aprotic solvent, add activator, inorganic salt co-solvent and pyridine, react at 80-100℃ for 4-8 hours, precipitate, filter, wash and dry to obtain polyamide precursor.

[0031] Further, the polar aprotic solvent is NMP; the inorganic salt co-solvent is LiCl, and its amount is 3% to 8% of the mass of NMP; the activator is phosphorus oxychloride, and pyridine is added. Example 8 shows the GPC results of the precursor obtained by this method.

[0032] Furthermore, in step S1, the number-average molecular weight Mn of the polyamide precursor is 3800-9200; the specific determination method and the results of each embodiment are shown in Test Example 1 and Table 1.

[0033] Further, in step S2, the solvent is NMP.

[0034] Further, in step S2, the concentration of the polyamide precursor in the solvent is 3-5 wt%; the mass ratio of the polyamide precursor to the artificial graphite matrix particles is (1.5-2.5):100.

[0035] Further, in step S3, the calcination process is as follows: in an inert atmosphere, the temperature is raised to 600-700℃, preferably 650℃, at a rate of 1-5℃ / min, and held for 1-4 hours; optionally, an intermediate heat-preserving platform is set at 300-400℃ for 0.5-1 hours during the heating process.

[0036] Thirdly, the present invention provides the application of the nitrogen-containing heterocyclic polyamide carbon precursor coated anode material described above in lithium-ion batteries.

[0037] The beneficial effects of this invention are: This invention prepares nitrogen-containing heterocyclic aromatic polyamide precursors via acyl chloride method, Yamazaki direct polycondensation method, or phosphoryl chloride activation method, and forms a nitrogen-doped amorphous carbon layer on the surface of artificial graphite. In the examples prepared in the range of 600–700°C, the pyridine nitrogen content, as measured by X-ray photoelectron spectroscopy N 1s peak, is 58%–72%. The 0.2C reversible specific capacity of the anode material is 380–390 mAh / g, compared to 355 mAh / g for the same batch of uncoated artificial graphite; the 5C capacity is approximately 11%–15% higher than that of uncoated artificial graphite; and the capacity retention after 500 cycles at 0.5C is 97%–98%. Attached Figure Description

[0038] Figure 1 The diagram shows the monomer structure of the representative nitrogen-containing heterocyclic polyamide precursor of this invention and the reaction route diagram of the acyl chloride / triphenyl phosphite (Yamazaki) direct polycondensation method; wherein, a is a monomer structure diagram; b is a reaction route diagram; Figure 2 The following are FT-IR images of the polyamide precursors (PPA, the same below) prepared in Examples 1 and 2 of this invention; Figure 3 The images shown are SEM and HR-TEM images of the negative electrode material prepared in Example 1 of this invention; where a represents the SEM image of the negative electrode material; and b represents the HR-TEM image of the negative electrode material. Figure 4 The XPS N 1s high-resolution spectra and peak fitting diagrams of the negative electrode materials prepared in Examples 1, 4, 6, Comparative Examples 2, 3, and 4 of this invention are shown. Figure 5 The graph shows the 500-cycle performance of the negative electrode materials prepared in Examples 1, 2, 4, 7, Comparative Examples 1, 2, and 3 of this invention at 0.5C. Figure 6 Comparison chart of the rate performance of the negative electrode materials prepared in Examples 1, 4, 7, Comparative Example 1, and Comparative Example 3 of the present invention; Figure 7 The graph shows the trend of pyridinic-N ratio in the DAP+PDC system of the present invention (Example 6, Example 1, Comparative Example 4) at different carbonization temperatures (550, 650, 900℃). Figure 8 This is a schematic diagram of the process of coating artificial graphite with nitrogen-containing heterocyclic polyamide precursor and carbonizing it to form a pyridine nitrogen-doped amorphous carbon layer according to the present invention. Detailed Implementation

[0039] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.

[0040] The monomer abbreviations used in this embodiment and comparative examples are as follows: DAP = 2,6-diaminopyridine; 3,5-DAP = 3,5-diaminopyridine; DAPYM = 4,6-diaminopyrimidine; TAP = 2,4,6-triaminopyridine; PPD = p-phenylenediamine; PDA = pyridine-2,6-dicarboxylic acid; PDC = pyridine-2,6-dicarboxylic chloride; TPC = terephthaloyl chloride; PPA = polyamide precursor; AG = artificial graphite.

[0041] Example 1 This embodiment provides a nitrogen-containing heterocyclic aromatic polyamide carbon precursor-coated anode material, and the preparation method is as follows: S1. In a 500 mL three-necked flask, add 200 mL of anhydrous NMP and 10 g of anhydrous LiCl, and stir until dissolved under nitrogen protection. Add 5.46 g (50 mmol) of 2,6-diaminopyridine (DAP), cool to 5 °C in an ice-water bath, and dissolve 9.69 g of pyridine-2,6-dicarboxylic acid chloride (PDC) (47.5 mmol, DAP:PDC = 1:0.95) in 50 mL of anhydrous NMP. Add the solution dropwise, heat to 25 °C, and stir for 4 h. Add 14 mL of triethylamine to neutralize the HCl, pour the solution into water to precipitate, filter, wash, and dry under vacuum at 80 °C to obtain 10.3 g of polyamide precursor, with a yield of 90%.

[0042] GPC:Mn=6800,PDI=2.1; FT-IR ( Figure 2 : 3290 cm⁻¹ (NH), 1665 cm⁻¹ (amide I band C=O), 1535 cm⁻¹ (amide II band), 1590 / 1445 cm⁻¹ (pyridine ring C=N / C=C), 812 cm⁻¹ (pyridine ring CH). Elemental analysis: N 23.0% (theoretical 23.3%).

[0043] The characteristic absorption of amide bonds and pyridine rings was observed in FT-IR, and the nitrogen content was found to be 23.0% by elemental analysis, which is close to the theoretical value of 23.3%. The above results are consistent with the structure of the target polyamide precursor.

[0044] S2. Dissolve 2g of polyamide precursor in 48mL of NMP, and add 100g of artificial graphite (D50=15.2μm, specific surface area 2.1m²). 2 / g), stirring for 2h to fully mix the polyamide precursor with the graphite particles, then slowly adding the dispersion to deionized water under stirring for anti-solvent precipitation, allowing the precursor to deposit and coat the surface of the graphite particles. Filtering, washing, and vacuum drying at 120℃ yielded pretreated graphite with a coating weight of 1.8wt%; S3. The pretreated graphite was calcined under a nitrogen atmosphere, heated to 350℃ at a rate of 2℃ / min and held for 0.5h, then heated to 650℃ and held for 2h to obtain a nitrogen-containing heterocyclic polyamide carbon precursor coated anode material with a carbonization yield of 48% and a carbon layer of 0.86wt%. Figure 3 -a is the SEM image of the negative electrode material obtained in this embodiment. In the image, the artificial graphite particles maintain an irregular blocky morphology, with no obvious agglomeration or adhesion; under this field of view, no obviously exposed rough areas are seen on the particle surface.

[0045] Figure 3 -b is the HR-TEM image of the negative electrode material obtained in this embodiment. In the image, lattice fringes are visible on the graphite matrix, and a coating layer with a thickness of about 8-12 nm and no obvious lattice fringes is visible on the surface; the coating layer is continuous in this field of view, and no obvious gaps or peeling are seen.

[0046] The negative electrode material obtained in this embodiment was characterized by XPS, and its N 1s high-resolution spectrum is shown below. Figure 4 As shown. Peak fitting of the N 1s spectrum showed that the relative contents of pyridinic nitrogen (68%), graphitic nitrogen (18%), pyrrolic nitrogen (10%), oxidized nitrogen (4%), and total nitrogen content of 6.2 at were in this material.

[0047] Example 2 This embodiment provides a nitrogen-containing heterocyclic aromatic polyamide carbon precursor-coated anode material, and the preparation method is as follows: S1. In a 500 mL three-necked flask, add 200 mL of anhydrous NMP, 10 g of anhydrous LiCl, and 20 mL of pyridine. Under nitrogen protection, add 5.46 g (50 mmol) of 2,6-diaminopyridine (DAP) and 8.36 g (50 mmol) of pyridine-2,6-dicarboxylic acid (PDA), and stir until dissolved. Slowly add 31.0 g (100 mmol, TPP / PDA = 2.0 equivalents) of triphenyl phosphite (TPP). Heat to 100 °C and stir for 5 h. The reaction solution changes from pale yellow to brownish-yellow, and the viscosity increases significantly. After cooling, pour into 500 mL of methanol to precipitate, filter, wash three times with methanol, and dry under vacuum at 80 °C. 10.8 g of PPA powder is obtained, with a yield of 90%.

[0048] GPC:Mn=4200,PDI=2.5; FT-IR ( Figure 2 ): Amide I band (1665cm) -1 ) and amide II band (1535cm) -1 Consistent with Example 1, the pyridine ring characteristic peak positions are the same, indicating that the products of both methods contain amide bonds and nitrogen-containing aromatic rings. The Mn of this precursor was measured to be 4200, while the Mn of the precursor in Example 1 was measured to be 6800.

[0049] Steps S2 and S3 in this embodiment are the same as in embodiment 1.

[0050] The carbonization yield of the anode material is 45%, and the carbon layer is 0.81 wt%. The carbon layer thickness is 8-14 nm.

[0051] XPS: pyridinic-N 65%, total N 5.8at.

[0052] Example 3 The only difference between this embodiment and Example 1 is that "5.46g (50mmol) 3,5-diaminopyridine" is used instead of "5.46g (50mmol) 2,6-diaminopyridine".

[0053] The molecular weight test results of the polyamide precursor obtained in this embodiment are as follows: GPC:Mn=9200, PDI=1.9; This Mn is higher than the 6800 measured in Example 1.

[0054] Carbonization yield 46%; XPS: pyridinic-N 58%, total N 5.5 at%; the proportion of pyridinic-N is lower than that of the 2,6-diaminopyridine system (68%) because the amine at the 3,5-position integrates into the carbon network in a different way than at the 2,6-position, and is partially converted into graphitic-N.

[0055] Example 4 The only difference between this embodiment and Example 1 is that "5.51g (50mmol) 4,6-diaminopyrimidine" is used instead of "5.46g (50mmol) 2,6-diaminopyrimidine".

[0056] GPC:Mn=5200,PDI=2.3; Carbonization yield 44%; XPS ( Figure 4 ): pyridinic-N accounts for 72%, and total N is 7.0 at%. The absolute content of pyridinic-N (7.0 × 72% = 5.04 at%) is the highest in the example carbonized at 650℃.

[0057] Example 5 The only difference between this embodiment and Example 1 is that "9.64g terephthaloyl chloride (47.5mmol, DAP:TPC=1:0.95)" is used instead of "9.69g pyridine-2,6-dicarboxylic acid chloride (47.5mmol, DAP:PDC=1:0.95)".

[0058] GPC:Mn=7500, PDI=2.0; Carbonization yield 50%; XPS: pyridinic-N accounts for 60%, and total N is 4.5 at%. Due to the dilution of nitrogen by TPC, the absolute contents of total N and pyridinic-N are lower than those of the all-nitrogen system.

[0059] Example 6 The only difference between this embodiment and embodiment 1 is that the "650℃ heat preservation for 2 hours" in step S3 is changed to "550℃ heat preservation for 2 hours".

[0060] Carbonization yield 55%; XPS ( Figure 4 ): pyridinic-N 75%, total N 7.5 at%. Lower carbonization temperature retains more pyridinic-N, but FT-IR shows 812 cm⁻¹. -1 The presence of residual absorption at 550℃ indicates that the sample retained more nitrogen-containing heterocyclic structures; therefore, this temperature data is only used to compare the effect of carbonization temperature and should not be used as the preferred basis for the preparation range of 600-700℃.

[0061] Example 7 The only difference between this embodiment and Example 1 is that "6.21g (50mmol) 2,4,6-triaminopyridine (TAP)" is used instead of "5.46g (50mmol) 2,6-diaminopyridine (DAP)"; and "7.27g (35.6mmol, TAP:PDC=1:0.71, with the acyl chloride group being under-added relative to the amino group to avoid gelation of the trifunctional monomer system)" is used instead of "9.69g (47.5mmol, DAP:PDC=1:0.95) pyridine-2,6-dicarboxylic acid chloride".

[0062] GPC:Mn=5500,PDI=3.4 (trifunctional monomeric branched structure, with a relatively wide molecular weight distribution). Carbonization yield 52%; carbon layer 12-20 nm; XPS: pyridinic-N 62%, total N 6.8 at.

[0063] Example 8 This embodiment provides a nitrogen-containing heterocyclic aromatic polyamide carbon precursor-coated anode material, and the preparation method is as follows: S1. Add 5.46 g (50 mmol) of DAP and 8.36 g (50 mmol) of PDA to 200 mL of NMP, along with 10 g of LiCl and 15 mL of pyridine. Under nitrogen protection, slowly add 8.0 g (52 mmol) of phosphorus oxychloride and react at 80 °C for 6 h. After cooling, pour the solution into water to precipitate, filter, wash, and dry. Obtain 9.5 g of polyamide precursor, yield 79%. GPC:Mn=3800, PDI=2.8; Steps S2 and S3 in this embodiment are the same as in embodiment 1.

[0064] Carbonization yield 43%; XPS: pyridinic-N 63%, total N 5.5 at%. Comparative Example 1 This comparative example uses artificial graphite directly without any coating.

[0065] Comparative Example 2 The only difference between this comparative example and Example 1 is that "5.46 g (50 mmol) of 2,6-diaminopyridine (DAP)" was replaced with "5.41 g (50 mmol) of p-phenylenediamine (PPD)"; and "9.64 g (47.5 mmol, PPD:TPC=1:0.95) of terephthaloyl chloride (TPC)" was replaced with "9.69 g (47.5 mmol, DAP:PDC=1:0.95) of pyridine-2,6-dicarboxylic chloride (PDC)".

[0066] Carbonization yield 52%; GPC:Mn=12500,PDI=2.2; XPS ( Figure 4 ): pyridinic-N is only 25% (a small amount of pyridinic-N comes from the random distribution of amide bond N during carbonization), total N is 3.2 at.

[0067] Comparative Example 3 This comparative example provides a polyacrylonitrile-coated graphite anode material, prepared by the following method: Dissolve 2g of polyacrylonitrile in DMF, then add 100g of artificial graphite (D50=15.2μm, specific surface area 2.1m²). 2 / g), stirred for 2h, and then the dispersion was slowly added to deionized water under stirring for anti-solvent precipitation, filtered, washed, and vacuum dried at 120℃ to obtain pretreated graphite; Pretreated graphite was calcined under a nitrogen atmosphere, heated to 350℃ at a rate of 2℃ / min and held for 0.5h, then heated to 650℃ and held for 2h to obtain polyacrylonitrile-coated graphite anode material with a carbonization yield of 55%. XPS ( Figure 4 ): pyridinic-N is only 28%.

[0068] Comparative Example 4 The only difference between this comparative example and Example 1 is that the "650℃ heat preservation for 2 hours" in step S3 is changed to "900℃ heat preservation for 2 hours".

[0069] XPS ( Figure 4 ): pyridinic-N only 15%, graphic-N 72%.

[0070] Test Example 1 The carbonization yield and nitrogen configuration of the anode materials obtained in Examples 1-8 and Comparative Examples 1-4 were tested using the following methods: Carbonization yield test: The polyamide precursor was placed alone in a nitrogen atmosphere and calcined according to the same heating program as in step S3. The carbonization yield = residual mass after calcination / mass before calcination × 100%, and was verified by thermogravimetric analysis (TGA, nitrogen atmosphere, heating to 900℃ at 10℃ / min).

[0071] Nitrogen configuration testing: The surface of the anode material was characterized by X-ray photoelectron spectroscopy (XPS, Al Kα source), with the binding energy corrected at C1s = 284.8 eV. The N 1s high-resolution spectrum was fitted with Shirley background subtraction and a Gaussian-Lorentzian hybrid line shape. The binding energies of pyridinic-N, pyrrolic-N, graphitic-N, and oxidized-N were set to 398.5 ± 0.2 eV, 400.1 ± 0.2 eV, 401.2 ± 0.2 eV, and 402–405 eV, respectively. The proportion of each nitrogen configuration was calculated as the ratio of the corresponding fitted peak area to the total N 1s peak area. The total nitrogen content was obtained by elemental quantification using XPS full spectrum.

[0072] Molecular weight determination: The number-average molecular weight (Mn) and molecular weight distribution index (PDI) of the polyamide precursors in the examples and comparative examples were determined by gel permeation chromatography (GPC). The mobile phase was N,N-dimethylformamide (DMF) containing 0.05 mol / L lithium bromide, the flow rate was 1.0 mL / min, the column temperature was 50 °C, and a differential refractive index detector was used. The results were calibrated with a narrow-distribution polystyrene standard. The reported molecular weights are apparent values ​​relative to the polystyrene standard. In the trifunctional branched system of Example 7, the reported Mn is the apparent molecular weight of its soluble component.

[0073] The test results are shown in Table 1: Table 1

[0074] From Table 1, we can see that: (1) Under the same DAP+PDA / PDC monomer framework, the pyridine nitrogen content of the materials obtained by the acyl chloride method (Example 1, Pyr-N 68%) and the Yamazaki direct polycondensation method (Example 2, Pyr-N 65%) is similar. The pyridine nitrogen content of the phosphoryl chloride activation method (Example 8) is 63%. The above results indicate that all three polycondensation methods can obtain materials with a pyridine nitrogen content greater than 50%.

[0075] (2) The pyridine nitrogen content of the 2,6-diaminopyridine system (Example 1) was 68%, and that of the 3,5-diaminopyridine system (Example 3) was 58%. This result indicates that under the polymerization and carbonization conditions used in this application, there is a correlation between the diamine isomer and the nitrogen configuration distribution after carbonization.

[0076] (3) The total nitrogen content of the 4,6-diaminopyrimidine system (Example 4) was 7.0 at, and the pyridine nitrogen content was 72%, both of which were the highest values ​​in the 650°C carbonization examples; its pyridine nitrogen content calculated by XPS atomic percentage was 5.04 at, which was higher than 4.22 at in Example 1.

[0077] (4) In the DAP+PDC system, when the carbonization temperatures are 550℃, 650℃ and 900℃, the pyridine nitrogen content is 75%, 68% and 15%, respectively, and the carbonization yield is 55%, 48% and 35%, respectively. The FT-IR of the sample at 550℃ still shows residual absorption of nitrogen-containing heterocycles, so this point is only used as a reference for the effect of temperature; this application uses 600~700℃, preferably 650℃, as the preparation range.

[0078] (5) The pyridine nitrogen content of Comparative Example 2 (PPD+TPC) was 25%, and that of Comparative Example 3 (PAN carbonization) was 28%, which is lower than that of the 650°C examples containing pyridine or pyrimidine rings (58%–72%). This comparison supports the fact that, under the conditions adopted in this application, the introduction of nitrogen-containing heteroaromatic monomers is beneficial to increasing the pyridine nitrogen content in the resulting carbon layer.

[0079] Based on the above results, under carbonization conditions of 650℃, the carbon layers obtained in the examples containing pyridine or pyrimidine rings had a pyridine nitrogen content of 58% to 72% and a carbonization yield of 43% to 52%; among them, the 4,6-diaminopyrimidine system had the highest surface nitrogen content and pyridine nitrogen content.

[0080] Test Example 2 Electrochemical performance test: (1) Assembly of button half cell: The negative electrode materials obtained in Examples 1-8 and Comparative Examples 1-4 were used as samples. They were mixed and slurryed according to the mass ratio of negative electrode material: Super P: CMC: SBR = 95: 1.5: 1.5: 2 and coated on copper foil (the areal loading based on active material is about 5 mg / cm²). 2 Vacuum dried at 110℃ for 12 hours, then rolled to a compacted density of approximately 1.55 g / cm³. 3 Electrodes were obtained by punching; CR2032 coin cells were assembled in an argon glove box using lithium metal sheets as counter electrodes, polyolefin membranes as separators, and 1 mol / L LiPF6 EC / DEC / EMC (volume ratio 1:1:1) solution as electrolyte; each cell was injected with approximately 80 μL of electrolyte, and after assembly, the cells were allowed to stand for 12 h before formation; three parallel cells were assembled for each sample group, and the data in Table 2 are the average values ​​of the parallel cells.

[0081] (2) Electrochemical parameter testing: voltage window is 0.005~2.0V (vs. Li / Li + The test temperature was 25℃, and the test was conducted after two cycles at 0.1C (1C=372mA / g). The initial coulombic efficiency was the ratio of the first-cycle delithiation capacity to the first-cycle lithiation capacity. Rate performance was tested in the order of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and back to 0.1C, with 10 cycles at each rate. The capacities listed in Table 2 for 0.2C, 0.5C, and 5C are the average values ​​of the last 5 cycles at the corresponding rates. The 500-cycle capacity retention rate was the ratio of the delithiation capacity at the 500th cycle to the delithiation capacity at the 1st cycle at 0.5C. The interface impedance R_interface was also measured. e was obtained by semicircular fitting in the high-frequency region of electrochemical impedance spectroscopy (EIS, frequency range 100kHz~10mHz, perturbation amplitude 5mV, measured after formation). This impedance includes contributions from the SEI film resistance and the interfacial charge transfer resistance. The fitting employed an equivalent circuit (Rs-(R_interface∥CPE)-W) consisting of parallel units of the solution resistance Rs, the interfacial resistance R_interface, and the constant-phase element CPE, and a Warburg diffusion element connected in series. The fitted resistance value was normalized to the area ratio impedance (Ω·cm) according to the electrode geometry. 2 ); The test results are shown in Table 2.

[0082] Table 2

[0083] The cycling performance of the anode materials prepared in Examples 1, 2, 4, 7, Comparative Examples 1, 2, and 3 after 500 cycles at 0.5C is shown in the figure. Figure 5As shown in the figure; a comparison of the rate performance of the negative electrode materials prepared in Examples 1, 4, 7, Comparative Example 1, and Comparative Example 3 is shown in the figure. Figure 6 As shown; Reference Figure 5 , Figure 6 As shown in Table 2, the reversible specific capacitance at 0.2C, 0.5C, and 5C, the capacitance retention rate after 500 cycles, and the interfacial impedance of each embodiment are all superior to those of the uncoated artificial graphite comparative example 1.

[0084] Based on the above results, under the conditions of the embodiments of this application, polyamide precursors containing pyridine or pyrimidine rings can form a nitrogen-doped amorphous carbon layer with a high pyridine nitrogen content on the surface of artificial graphite after carbonization at 650°C. The reversible specific capacity, rate capacity, 500-cycle capacity retention, and interfacial impedance of the resulting material are all superior to those of uncoated artificial graphite.

[0085] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.

Claims

1. A nitrogen-containing heterocyclic polyamide carbon precursor-coated anode material, characterized in that, The negative electrode material includes artificial graphite matrix particles and a pyridine nitrogen-doped amorphous carbon layer coated on the surface of the artificial graphite matrix particles. The pyridine nitrogen-doped amorphous carbon layer is formed by carbonization of a polyamide precursor; The polyamide precursor is prepared by amidation polycondensation reaction of nitrogen-containing aromatic polyamine monomer and aromatic polyacid monomer, and the main chain contains amide bonds and nitrogen-containing aromatic rings. The aromatic polyacid monomers are aromatic polyacid monomers or aromatic polyacryl chloride monomers; According to the N 1s peak determination by X-ray photoelectron spectroscopy, pyridine nitrogen accounts for more than 50% of the total nitrogen content in the pyridine nitrogen-doped amorphous carbon layer.

2. The nitrogen-containing heterocyclic polyamide carbon precursor-coated negative electrode material as described in claim 1, characterized in that, The nitrogen-containing aromatic polyamine monomers include one or more of 2,6-diaminopyridine, 3,5-diaminopyridine, 2,4,6-triaminopyridine, and 4,6-diaminopyrimidine.

3. The nitrogen-containing heterocyclic polyamide carbon precursor-coated anode material as described in claim 1, characterized in that, The aromatic polyacid monomer is pyridine-2,6-dicarboxylic acid; The aromatic polyacryl chloride monomer includes one or more of pyridine-2,6-dicarboxylic acid chloride and terephthaloyl chloride.

4. The nitrogen-containing heterocyclic polyamide carbon precursor-coated negative electrode material as described in claim 1, characterized in that, Of the nitrogen-containing aromatic polyamine monomers and aromatic polyacid monomers, at least one monomer contains a nitrogen-containing heteroaromatic ring.

5. The nitrogen-containing heterocyclic polyamide carbon precursor-coated negative electrode material as described in claim 1, characterized in that, The D50 of the artificial graphite matrix particles is 10–20 μm; The thickness of the pyridine nitrogen-doped amorphous carbon layer is 8–20 nm. The surface nitrogen atom content of the pyridine nitrogen-doped amorphous carbon layer is 4.5 to 7.5 at.

6. The nitrogen-containing heterocyclic polyamide carbon precursor-coated negative electrode material as described in claim 1, characterized in that, The pyridine nitrogen-doped amorphous carbon layer contains more than 60% pyridine nitrogen in its total nitrogen content; the surface nitrogen atom content is 5 to 7.5 at.

7. The nitrogen-containing heterocyclic polyamide carbon precursor-coated negative electrode material as described in claim 1, characterized in that, The nitrogen-containing aromatic polyamine monomer is 2,6-diaminopyridine and / or 4,6-diaminopyrimidine, and the aromatic polyacid monomer is pyridine-2,6-dicarboxylic acid and / or pyridine-2,6-dicarboxylic chloride.

8. A method for preparing a nitrogen-containing heterocyclic polyamide carbon precursor-coated anode material, used to prepare the nitrogen-containing heterocyclic polyamide carbon precursor-coated anode material according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Amidation condensation reaction of nitrogen-containing aromatic polyamine monomers and aromatic polyacid monomers is carried out to prepare polyamide precursors; S2. Add the polyamide precursor obtained in S1 to the solvent, add artificial graphite matrix particles, stir, and then remove the solvent or add an antisolvent to deposit the precursor to obtain pretreated artificial graphite particles. S3. The pretreated artificial graphite particles are calcined in an inert atmosphere to obtain a negative electrode material coated with nitrogen-containing heterocyclic polyamide carbon precursor.

9. The method for preparing the anode material coated with a nitrogen-containing heterocyclic polyamide carbon precursor as described in claim 8, characterized in that, In step S1, the molar ratio of the nitrogen-containing aromatic polyamine monomer to the aromatic polyacid monomer is 1:(0.7-1.0), or the equivalent ratio of the functional groups of the amino group of the nitrogen-containing aromatic polyamine monomer to the carboxyl or acyl chloride group of the aromatic polyacid monomer is 1:(0.45-1.0). The amidation polycondensation reaction includes any one of the following: acyl chloride method, Yamazaki direct polycondensation method, and phosphoryl chloride activation method.

10. The method for preparing the anode material coated with the nitrogen-containing heterocyclic polyamide carbon precursor as described in claim 9, characterized in that, The specific steps of the acyl chloride method are as follows: under an inert atmosphere, nitrogen-containing aromatic polyamine monomers are dissolved in NMP, LiCl is added, the mixture is cooled to 0-10°C, aromatic polyacyl chloride monomers are added, and the mixture is reacted at room temperature for 2-8 hours. Triethylamine is added, and the mixture is precipitated, filtered, washed, and dried to obtain a polyamide precursor. The amount of LiCl used is 3%-8% of the mass of NMP. The specific steps of the Yamazaki direct polycondensation method are as follows: aromatic polyacid monomers and nitrogen-containing aromatic polyamine monomers are added to a polar aprotic solvent, a condensing agent, pyridine, and an inorganic salt co-solvent are added, and the reaction is carried out at 80-120°C for 3-8 hours. After precipitation, filtration, washing, and drying, a polyamide precursor is obtained. The polar aprotic solvent is NMP; the inorganic salt co-solvent is LiCl, and its amount is 3%-8% of the mass of NMP; the condensing agent is triphenyl phosphite. The specific steps of the phosphoryl chloride activation method are as follows: aromatic polyacid monomers and nitrogen-containing aromatic polyamine monomers are added to a polar aprotic solvent, an activator, an inorganic salt co-solvent, and pyridine are added, and the mixture is reacted at 80-100°C for 4-8 hours. After precipitation, filtration, washing, and drying, a polyamide precursor is obtained. The polar aprotic solvent is NMP; the inorganic salt co-solvent is LiCl, and its amount is 3%-8% of the mass of NMP; the activator is phosphorus oxychloride.

11. The method for preparing the anode material coated with a nitrogen-containing heterocyclic polyamide carbon precursor as described in claim 9, characterized in that, In step S1, the number-average molecular weight Mn of the polyamide precursor is 3800-9200; In step S2, the solvent is NMP; In step S2, the concentration of the polyamide precursor in the solvent is 3-5 wt%; the mass ratio of the polyamide precursor to the artificial graphite matrix particles is (1.5-2.5):

100. In step S3, the calcination process is as follows: in an inert atmosphere, the temperature is increased to 600-700℃, preferably 650℃, at a rate of 1-5℃ / min, and held for 1-4 hours.

12. The application of the nitrogen-containing heterocyclic polyamide carbon precursor-coated anode material as described in any one of claims 1-7 in lithium-ion batteries.

Citation Information

Patent Citations

  • Nitrogen-containing artificial graphite negative electrode material, preparation method and application thereof, and battery

    CN114195144A

  • A nitrogen-doped graphitized carbon material and a preparation method thereof

    CN117756107B